Development of a Pilot Grants Program in Social Determinants of Health in American Indian Health: A Program for Increasing the Representation of Underrepresented Groups in Funded Research - Becker, Alyson E. (J Res Adm, 2018)
The problem statement for this manuscript is to describe the literature on grant funding for underrepresented investigators, particularly American Indians, and detail the CRCAIH Pilot Grant Program and its success in developing underrepresented researchers (e.g. American Indian, early stage investigators). Grant funding is increasingly difficult to receive and the demographics of NIH grant awardees have shifted in recent decades to funding investigators that are more experienced. Additionally, racial disparities in awardees exist, particularly among American Indian (AI) researchers. Pilot grant funding mechanisms can be used by early stage investigators to collect preliminary data, which is beneficial for applying for NIH grants. The Collaborative Research Center for American Indian Health (CRCAIH) Pilot Grant Program (PGP) was aimed to increase research on the topic of social determinants of health in AI population health. Since there are no existing procedures for creating a PGP, CRCAIH created a PGP, and the processes are detailed here. Over four years, the CRCAIH PGP funded 15 projects with 47% of PIs or Co-PIs self-reporting as AI. Future directions for the CRCAIH PGP, including a mentoring program to provide more guidance and capacity building to the investigators, are also detailed.